Reflexivity gradient—Consciousness knowing itself - Josipovic, Zoran (Frontiers in Psychology, 2024)
Some consider phenomenal consciousness to be the great achievement of the evolution of life on earth, but the real achievement is much more than mere phenomenality. The real achievement is that consciousness has woken up within us and has recognized itself, that within us humans, consciousness knows that it is conscious. This short review explores the reflexivity of consciousness from the perspective of consciousness itself—a non-conceptual nondual awareness, whose main property is its non-representational reflexivity. In light of this nondual reflexivity, different types of reflexivity proposed by current theories can be seen as a gradation of relational or transitive distances between consciousness as the knower and consciousness as the known, from fully representational and dual, through various forms of qualified monism, to fully non-representational and nondual.